Feminine consciousness and Greek spirit in Hegel - Macquarrie, Heather D (University of Ottawa (Canada), 2009)
Hegel's inherently universal conception of modern subjectivity recognizes the principle of the modern subject is "the self-sufficient and inherently infinite personality of the individual." Hegel's deepest and most genuine intentions require all humanity to lead a universal life of full and concrete personhood in accordance with the definition of human nature as a concrete unity of substance and subject. These are not fulfilled in his treatment of feminine consciousness. Women have not been fully reconciled with modern subjectivity. The thesis investigates opportunities to systematically resolve the inconsistencies inherent in Hegel's feminine consciousness, consistent with his logical imperatives and genuine intentions. The main contribution will be to locate sources of the problem that have been identified but not fully analysed in the literature of feminist philosophy. Beyond the standard references (The Phenomenology of Mind and Philosophy of Right) the thesis examines other works, notably, Science of Logic and relevant passages from throughout the Realphilosophie including history, aesthetics, and the philosophy of religion. The problem is situated within the framework of Hegel's developmental account of historical Spirit. The special relationship between feminine consciousness and Greek Spirit is studied in Hegel's Antigone story. She represents the Beautiful Individual whose freedom lies in self-sacrifice for universal ends of the community. Hegel's theory of modern ethical life once again casts women in the dutiful role of Beautiful Individuals and leaves them to perform the essential function of preserving objective Spirit, at the expense of their own self-consciousness. The thesis studies Hegel's contradictory treatment of women in the larger context of his effort to systematically resolve the ancient conflict of Nature and Spirit integral to the character of the ancient subject. Antigone reappears as a sign that, notwithstanding the modern principle of subjective freedom and Christian egalitarian principles that underlie the secular world, Hegel was unable to rationally and logically resolve this problem. The development within the theory of modern ethical life of a responsible standpoint towards Nature and finitude is necessary, for Hegel's intentions for women and men to be realized.
Keywords: Philosophy.